Дослідження змін властивостей вольфрамових сплавів під впливом імпульсних нагрівів - Shalomeev, V. A.; Korobko, O. V.; Vinichenko, V. S.; Parkhisenko, D. I. (Physico- Technological Institute of Metals and Alloys of the NAS of Ukraine, 2025)
The improvement of the design of modern heat engines is characterized by the expansion of the use of heat-resistant fibrous metal composites (MCM). An important feature of these materials is that their properties can be purposefully changed in the necessary directions depending on the loading scheme of a particular part. The component that largely determines the strength and technological properties of such a composite is the fibers. Currently, the requirements for the properties of reinforcing fibers are quite fully met by tungsten alloy wires, and the use of short pulse heating is promising for the formation of the composite. However, in the case of irrationally set values ​​of the parameters of the formation process, pulse heating can lead to an unjustified decrease in the properties of the fibers, in particular strength and plasticity at temperatures around 20°C. Therefore, in order to rationally select the alloy grade for fibers and CM formation modes that do not lead to an unjustified decrease in the properties of reinforcing fibers, this work studied the influence of pulse heating parameters, in particular, the heating rate and the maximum achievable temperature on the properties of fibers from tungsten-rhenium and molybdenum-rhenium alloys. To investigate changes in fiber properties, under the influence of technological heating, the heating of fibers was simulated, which occurs during the CM formation process by passing electric current pulses of different power through their samples. It was found that reinforcing fibers from a tungsten-rhenium alloy containing about 5% rhenium become brittle after pulse heating to temperatures (above 2000°C) necessary for the formation of a defect-free MKM structure, and wires from tungsten-rhenium alloys containing about 27% rhenium retain their plasticity at a temperature of 20°C after pulse heating up to melting temperatures.